2009
DOI: 10.1007/s12088-009-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

A 70-kDa molecular chaperone, DnaK, from the industrial bacterium Bacillus licheniformis: gene cloning, purification and molecular characterization of the recombinant protein

Abstract: The heat shock protein 70 (Hsp70/DnaK) gene of Bacillus licheniformis is 1,839 bp in length encoding a polypeptide of 612 amino acid residues. The deduced amino acid sequence of the gene shares high sequence identity with other Hsp70/DnaK proteins. The characteristic domains typical for Hsps/DnaKs are also well conserved in B. licheniformis DnaK (BlDnaK). BlDnaK was overexpressed in Escherichia coli using pQE expression system and the recombinant protein was purifi ed to homogeneity by nickel-chelate chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…CD spectrum analysis of M. haemofelis rDnaK revealed two minima (at 208 and 222 nm), suggesting that it consisted mostly of ␣-helices (8), which is in good agreement with known DnaK structures, e.g., of E. coli (Protein Database identiy [PDB ID]: 2KH0) and G. kaustophilus (PDB ID: 2V7Y). The structure profile of M. haemofelis rDnaK was insensitive to a change in the presence of nucleotide, as has been shown before for Bacillus licheniformis DnaK (13), and also in the presence of K ϩ and Mg 2ϩ ions. The thermal denaturation of M. haemofelis rDnaK was characterized by two temperature transitions.…”
Section: Discussionsupporting
confidence: 76%
“…CD spectrum analysis of M. haemofelis rDnaK revealed two minima (at 208 and 222 nm), suggesting that it consisted mostly of ␣-helices (8), which is in good agreement with known DnaK structures, e.g., of E. coli (Protein Database identiy [PDB ID]: 2KH0) and G. kaustophilus (PDB ID: 2V7Y). The structure profile of M. haemofelis rDnaK was insensitive to a change in the presence of nucleotide, as has been shown before for Bacillus licheniformis DnaK (13), and also in the presence of K ϩ and Mg 2ϩ ions. The thermal denaturation of M. haemofelis rDnaK was characterized by two temperature transitions.…”
Section: Discussionsupporting
confidence: 76%
“…Because the gram‐negative bacterium E. coli has been primarily used for previous investigations of DnaK and its co‐chaperones, therefore relatively few studies using gram‐positive bacterial DnaK chaperone systems have been reported . For example, Bacillus subtilis dnaK operon mutants can grow within a temperature range of 16°C–52°C and fail to form colonies above 52°C, in contrast to E. coli dnaK null mutants .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few DnaK chaperone systems from gram‐positive bacteria have been investigated with respect to this property. However, it has been observed that the activity of the DnaK chaperone system in gram‐positive bacteria appears to vary with the species . The Clostridium acetobutylicum DnaK chaperone system is able to refold chemically denatured luciferase, albeit with a lower yield than the E. coli DnaK chaperone system .…”
mentioning
confidence: 99%
“…The role of dnak in thermoregulation is well established by gene expression studies at mRNA level ( Wetzstein et al, 1992 ) and deletion mutation studies ( Singh et al, 2007 ). Enhancement of thermotolerance in the heterologous system has been reported in various organisms like Escherichia coli ( Liang et al, 2009 ), tobacco ( Ono et al, 2001 ), Arabidopsis thaliana ( Montero-Barrientos et al, 2010 ) and Rice ( Uchida et al, 2008 ). dnaK gene from Trichoderma harzianum has been found to enhance tolerance to drought and freezing stress in poplar ( Takabe et al, 2008 ).…”
Section: Introductionmentioning
confidence: 98%
“…Five major families of Hsps are recognized; Hsp 70 (DnaK) family; the chaperonins (GroEL and Hsp 60); Hsp 90 family; Hsp 100 (Clp) family and the small Hsp (sHsp) family ( Wang et al, 2004 ). DnaK proteins are involved in de novo protein folding, membrane translocation, formation and disassembly of protein complexes and degradation of misfolded proteins ( Liang et al, 2009 ). DnaK consists of a highly conserved NH 2 -terminal ATPase domain, COOH-terminal substrate binding domain and a α-helical domain.…”
Section: Introductionmentioning
confidence: 99%